2020
DOI: 10.2174/1871520620666200721125820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Apoptotic Activities of New 2(3H)-benzoxazolone Derivatives in Breast Cancer Cells

Abstract: Background: 2(3H)-Benzoxazolone derivatives are preferential structural blocks in pharmacological probe designing with possibility of modifications at various positions on the core structure. Benzoxazolones showed various biological activities such as analgesics, anti-inflammatory and anti-cancer. Objective: In the present work, we have prepared new Mannich bases of 2(3H)-benzoxazolone derivatives and evaluated their cytotoxicities and proapoptotic properties in MCF-7 breast cancer cell line. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Ivanova et al, chalcone compounds with benzoxazolone in their structure have antileukemic effects through triggering apoptotic cell death [11]. Furthermore, Erdag et al discovered that Mannich bases of benzoxazolone produced on the third position via Mannich reaction exhibit cytotoxic effects on the MCF-7 breast cancer cell line [12]. In the same study, it was reported that the chemical characteristics of the substituents at the fifth position of the benzoxazolone ring can affect the apoptotic cell pathways extrinsically or intrinsically.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ivanova et al, chalcone compounds with benzoxazolone in their structure have antileukemic effects through triggering apoptotic cell death [11]. Furthermore, Erdag et al discovered that Mannich bases of benzoxazolone produced on the third position via Mannich reaction exhibit cytotoxic effects on the MCF-7 breast cancer cell line [12]. In the same study, it was reported that the chemical characteristics of the substituents at the fifth position of the benzoxazolone ring can affect the apoptotic cell pathways extrinsically or intrinsically.…”
Section: Introductionmentioning
confidence: 99%